Proceedings of the 5th International Conference on Indonesian Social and Political Enquiries, ICISPE 2020, 9-10 October 2020, S 2021
DOI: 10.4108/eai.9-10-2020.2304782
|View full text |Cite
|
Sign up to set email alerts
|

The Change of Investment Behavior during Covid-19 Pandemic in Indonesia Stock Market

Abstract: The emergence of the Covid-19 Pandemic has made the Indonesian stock market unstable. Investment behavior in a person can change at an unknown time. By incorporating planned behavior theory and perceived risk theory, this research analyzed the change of investment behavior from six different variables. Therefore, the purpose of this research is to compare the investors' behavior before and during Covid-19 Pandemic in Indonesia Stock Market. Those are investor's attitudes, subjective norms, perceived behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
2
0
1
Order By: Relevance
“…In other words, during the pandemic both male and female act more sensitive to risk or take actions that reduce risk in investing, especially investing in stocks. These results are in line with the results of research conducted by Komalasari, Manik and Ganiarto (2020). In their research, they concluded that there is a significant difference in investors' perceived risk before and during the Covid-19 pandemic, where investors considered risk (reducing risk) during the pandemic compared to before the pandemic.…”
Section: Resultssupporting
confidence: 81%
“…In other words, during the pandemic both male and female act more sensitive to risk or take actions that reduce risk in investing, especially investing in stocks. These results are in line with the results of research conducted by Komalasari, Manik and Ganiarto (2020). In their research, they concluded that there is a significant difference in investors' perceived risk before and during the Covid-19 pandemic, where investors considered risk (reducing risk) during the pandemic compared to before the pandemic.…”
Section: Resultssupporting
confidence: 81%
“…Financial markets experienced a liquidity crisis during the outbreak – investors had trouble selling their assets quickly without heavy losses. This can lead to a higher cost of capital because investors require a higher return on their investments to compensate for the liquidity risk (Komalasari et al , 2021; Nguyen et al , 2021).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Pandemi memengaruhi kondisi kesehatan, sosial, dan ekonomi dunia karena timbulnya ketidakpastian global. Kekhawatiran investor terkait ketidakpastian global akibat Covid-19 membuat investor lebih berhati-hati dalam membuat keputusan dan mengurangi aktivitas investasi (Komalasari et al, 2021). Hal ini berpengaruh kepada seluruh pasar modal di dunia yang mengalami penurunan kinerja secara signifikan, termasuk pasar modal di Indonesia.…”
Section: Pendahuluanunclassified